Corporate Growth Strategy for Sustainable Wedding Decoration Businesses in Indonesia - Romi Aldi; Moh Nopriandi (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study examines corporate growth strategies in the wedding decoration industry with a focus on sustainability, innovation, and local cultural adaptation. Using a qualitative descriptive approach, the research explores how wedding decoration companies in Indonesia, particularly in Nusa Tenggara Barat, integrate creative business models and environmentally responsible practices to achieve long-term competitiveness. Data were collected through interviews, observations, and document analysis from leading local enterprises, including Cristall Party Planner and Yazid Decoration. The findings reveal that sustainable growth in this sector is driven by four key factors: product innovation, digital marketing optimization, partnership building with wedding organizers and venues, and the incorporation of local cultural elements into modern design concepts. In addition, the study highlights the implementation of green wedding principles—such as reducing waste, reusing decorative materials, and sourcing locally—which contribute to both environmental protection and brand differentiation. The application of the Ansoff Matrix framework demonstrates how businesses can balance market expansion with risk management through market penetration, product diversification, and strategic collaboration. This study concludes that sustainability-oriented innovation and adaptive corporate growth strategies are essential for maintaining competitiveness in Indonesia’s creative wedding industry.